Overexpression of lily HsfA3s in Arabidopsis confers increased thermotolerance and salt sensitivity via alterations in proline catabolism. (31st January 2018) - Wu, Ze; Liang, Jiahui; Wang, Chengpeng; Zhao, Xin; Zhong, Xionghui; Cao, Xing; Li, Guoqing; He, Junna; Yi, Mingfang
Abstract : Overexpression of lily HsfA3 s in Arabidopsis leads to changes in proline metabolism mediated via alterations in the regulation of specific bZIP transcription factors and confers increased thermotolerance and salt sensitivity. Abstract: Although HsfA3 (heat-stress transcription factor A3) is well characterized in heat stress, its roles in other abiotic stresses are less clear. In this study, we isolated two homologous HsfA3 genes, LlHsfA3A and LlHsfA3B, from lily ( Lilium longiflorum ). Both genes were induced by heat stress, but not by salt stress. Overexpressing LlHsfA3A in Arabidopsis enhanced its basal and acquired thermotolerance, while overexpressing LlHsfA3B just enhanced its acquired thermotolerance. In both cases, overexpressing plants showed hypersensitivity to salt stress, and a lack of sucrose exacerbated this salt sensitivity. Using a transient assay, the opposite effects were observed in lily. Further analysis revealed that either LlHsfA3A or LlHsfA3B overexpression altered normal proline accumulation. During heat treatments, proline increased in wild-type Arabidopsis plants, but no such increase was detected in transgenic plants that showed better basal or acquired thermotolerance. Under salt stress, proline accumulation was decreased in Arabidopsis and lily with the overexpression of LlHsfA3A or LlHsfA3B . Proline catabolism was activated by overexpression, and both LlHsfA3A and LlHsfA3B affected proline oxidation via regulation of AtbZIP11, AtbZIP44, and AtbZIP53 to activate AtproDH1 and AtproDH2 in transgenic Arabidopsis. Taken together, our results suggested that overexpression of LlHsfA3A or LlHsfA3B caused opposite effects on heat and salt tolerance, which may implicate proline catabolism.